Eosinophilic Pneumonia in a Patient with Ulcerative Colitis - Patel, Keyur B. (Radiol Case Rep, 2015)
We present the case of 16-year-old woman with a 2-month history of ulcerative colitis who presented with cough, fever, dyspnea on exertion, and nasal congestion. Computed tomography of the chest demonstrated peripheral alveolar opacities with relative sparing of the central portions of the lungs. The clinical and radiologic findings raised the suspicion of eosinophilic pneumonia, possibly drug-related. The patient had recently been started on a trial of Mesalamine (5-aminosalicylic acid or 5-ASA) for treatment of her ulcerative colitis 2 months ago. The patient's condition improved after discontinuation of mesalamine and treatment with prednisone. The clinical course and radiologic features supported the presumptive diagnosis of Mesalamine-induced eosinophilic pneumonia.